Intensive care management of organophosphorus poisoning patients: an experience from tertiary care centre - Nazima, Syed Nazima; Bashir, Yasir; Nabi, Shakeeb; Bashir, Nusrat (International Journal of Advances in Medicine, 2018)
Background: Organophosphate (OP) insectide poisoning results from occupational, accidental and intentional exposure. The mortality rate of OP poisoning is high. Early diagnosis and appropriate treatment is often lifesaving. Methods: This study “Intensive care management of organophosphorous poisoning in Govt. medical college Srinagar (Sgr) hospital was a prospective one and was conducted over a period of two. All the patients with a provisional diagnosis of Organophosphorous poisoning who reported to the medical casualty and intensive care unit of SMHS hospital Sgr were included in this study. Results: Out of a total of 1258 Organophosphorous poisoning cases, males were (34.5%) and females were (65.5%). Suicidal mode of poisoning was most common in our patients and constituted 63.20%. Out of 254 Organophosphorous poisoned patients admitted in ICU, 184 survived and 70 expired. Therefore, mortality rate for Organophosphorous poisoned patients who needed mechanical ventilation was 27.55. Conclusions: OP poisoning is a serious problem in Kashmir Valley. Efforts should be directed towards rapid diagnosis and management of this condition. Additionally, close intensive monitoring of these patients for early recognition of respiratory failure which is one of the serious complication of OP poisoning with intensive care support will help in decreasing the mortality rate in these patients.